Advice seeking and loaning of money related to relapse in recovery homes. (16th September 2020) - Jason, Leonard A.; Guerrero, Mayra; Salomon‐Amend, Meghan; Lynch, Gabrielle; Stevens, Ed; Light, John M.; Stoolmiller, Mike
Abstract: Recovery homes help individuals who have completed substance use treatment programs re‐integrate back into the community. However, it is unclear what factors determine who will succeed in these settings and how these factors may be reinforced or undermined by the social interactions and social networks between residents living in the Oxford House recovery homes. In an effort to better understand these factors, the current study evaluated (a) the extent to which the density of social networks (i.e., friendship, willingness to loan money, and advice‐seeking relationships) is associated with social capital (i.e., sense of community, quality of life, hopefulness, self‐efficacy), and (b) whether the density of social networks predicts relapse over time. Among the findings, willingness to loan money was positively associated with all four individual‐level social capital variables, suggesting that availability of instrumental resources may be important to ongoing recovery. To test whether these house‐level social network factors then support recovery, a survival analysis was conducted, finding associations between relapse risk and the network densities over a 28‐month span. In particular, more dense advice‐seeking networks were associated with higher rates of relapse, suggesting that the advice‐seeking might represent a sign of organisational house problems, with many residents unsure of issues related to their recovery. In contrast, more dense loaning networks were associated with less relapse, so willingness to lend money could be measuring a willingness to help those in need. The implications of these findings are discussed.